Characteristics of large-area porous media burner applicable to direct-fired non-oxidizing annealing furnace. (5th March 2021) - Lee, Min Jung; Noh, Dong Soon; Lee, Eun Kyung
Highlights: A large-area PMB was investigated for a direct-fired non-oxidizing furnace. The crossover temperature could be a criterion for combustion mode changes. Radiant heat flux and effective emissivity were measured for fuel-rich conditions. Periodic on-off operation tests were performed to evaluate the durability of PMB. Abstract: In the continuous steel strip annealing process, uniform and rapid heating in a non-oxidizing atmosphere is required to improve product quality and productivity while reducing emissions and saving energy. In this study, the combustion characteristics of a porous media burner (PMB) with a large surface area (40 × 25 cm 2 ) are studied for application in a non-oxidizing annealing furnace using a model furnace. The furnace temperature is controlled according to the variation of the thermal load per unit area (475–928 kW / m 2 ) and equivalence ratio (1.05–1.35), and its range was 1130–1330 °C at a 0% oxygen concentration or non-oxidizing atmosphere. In high furnace temperature conditions, the PMB surface temperature and radiant heat flux are also measured. Based on the results, the combustion mode changes, which implies a transition from the surface to the submerged combustion mode of the PMB, and were directly compared with the crossover temperature. The criteria for the transition of the PMB combustion mode are also proposed using basic radiation theory. Moreover, the effective emissivity of the porous media is evaluated from the measurement of the radiant heat flux, and its value was 0.845. Finally, the PMB durability is evaluated through a cyclic on-off operation test and consequently, the operational safety was confirmed.